2017
DOI: 10.1080/03610926.2013.775306
|View full text |Cite
|
Sign up to set email alerts
|

The Lamé class of Lorenz curves

Abstract: In this paper, the class of Lamé Lorenz curves is studied. This family has the advantage of modeling inequality with a single parameter. The family has a double motivation: it can be obtain from an economic model and from simple transformations of classical Lorenz curves. The underlying cumulative distribution functions have a simple closed form, and correspond to the Singh-Maddala and Dagum distributions, which are well known in the economic literature. The Lorenz order is studied and several inequality and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…One other metric in economy is the Gini index to quantify inequalities based on Lorenz curves. In many cases this can be modeled efficiently with Lamé curves or superellipses [34,35]. Recently, it was shown that Gini and Theil indices from economy can also be used in the study of natural phenomena.…”
Section: Allometry Laws Of Physics and Production Functionsmentioning
confidence: 99%
“…One other metric in economy is the Gini index to quantify inequalities based on Lorenz curves. In many cases this can be modeled efficiently with Lamé curves or superellipses [34,35]. Recently, it was shown that Gini and Theil indices from economy can also be used in the study of natural phenomena.…”
Section: Allometry Laws Of Physics and Production Functionsmentioning
confidence: 99%
“…Известно, что модель (13) хорошо зарекомендовала себя при изучении неравенства доходов населения (Sarabia, Jordá and Trueba, 2013).…”
Section: модель кривой паретоunclassified
“…It is known that the model(13) has shown good results in the study of inequality of incomes of the population (Sarabia, Jordá and Trueba, 2013).…”
Section: The Pareto Curve Modelmentioning
confidence: 99%